Type of lymphadenectomy does not influence survival in pIa NSCLC patients who underwent VATS lobectomy: Results from the national VATS group database. (December 2022) - Chiappetta, Marco; Lococo, Filippo; Sperduti, Isabella; Tabacco, Diomira; Meacci, Elisa; Curcio, Carlo; Crisci, Roberto; Margaritora, Stefano; ,
Highlights: The appropriate lymphadenectomy in pT1a NSCLC is debated. Sampling and mediastinal radical dissection (MRLD) are equivalent for OS. Sampling and MRLD are equivalent for OS and DFS in solid nodules. ECOG score, SUVmax and grading are prognostic factors in these patients. Abstract: Introduction: Stage Ia presents an optimal survival rate after surgical resection, but the type of lymphadenectomy to use in these patients is still debated. The aim of this study is evaluate if one type of lymphadenectomy adopted influences survival in patients who underwent VATS lobectomy for stage Ia NSCLC. Methods: Clinical and pathological data from pIa patients in the prospective VATS Italian nationwide registry were reviewed and analysed. Patients and tumour characteristics, type of lymphadenectomy (sampling or radical nodal dissection, MRLD), were collected and correlated to Overall Survival(OS) and Disease free Survival(DFS). The Kaplan-Meier product-limit method was used to estimate OS and DFS and the log-rank test was adopted to evaluate the differences between groups. A propensity match was performed to reduce bias due to the retrospective study design. Results: The final analysis was conducted on 2039 patients, 179 died during follow-up, recurrence rate was 13%. MRLD was performed in 1287(63.1%)patients. The univariable analysis identified as favourable prognostic factors for OS the female sex(p = 0.023), low ECOG-score(0.008), low SUVmax(p < 0.001), GGO appearance(p < 0.001), pT < 2 cm(p = 0.002) and low tumour grading(p = 0.002). The multivariable analysis confirmed as independent prognostic factors low ECOG-score(p = 0.012), low SUVmax(p < 0.001) and low tumour grading(p < 0.001). Analysing survival in patients with solid/sub-solid nodules and after propensity score matching for pTdimension and number of N2 resected lymphnodes, no OS differences were present comparing sampling vs MRLD. Conclusion: Survival in pIa patients seems to be determined by patient and tumour characteristics such as performance status, grading and SUVmax. Type of lymphadnectomy did not seem to be correlated with OS in these patients.